Application of the psychological continuum model to understand customers' involvement and satisfaction in a fitness center - Joseph, Jacklyn; Yusof, Aminuddin; Soh, Kim Geok (Penerbit Universiti Malaysia Pahang, 2017)
This research examined how customers’ perceptions of service quality influence the degree of their involvement and psychological connection to a sport activity at a fitness center by applying the Psychological Continuum Model (PCM). Research instruments consisted of the PCM and SERVQUAL and administered to customers at a fitness centre in Malaysia (n = 248). In terms of sport involvement, the results showed most subjects are in the level of attachment. Results showed all dimensions of service quality have negative mean scores which mean customers are dissatisfied will all aspects of service quality at the fitness centre. A one-way ANOVA showed differences in satisfaction with service quality based on the PCM level of involvement for tangible, reliability, responsiveness and empathy dimensions of service quality. Customers at the higher level of involvement (allegiance) reported less dissatisfaction with the tangible, responsiveness, empathy and reliability dimensions of service quality compared with those at the awareness level.